1978
DOI: 10.1007/bf00129420
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation and improvement of teaching in higher education

Abstract: Four procedures to evaluate teaching (by students, peers, video-recordings, and direct measurements of student learning) and three uses of the evaluation results (improving teaching, personnel decisions, course handbooks) are reviewed in the light of empirical evidence. Special emphasis is placed on the timing and validity of student ratings and the instruments used. Since none of the procedures appear sufficient in and by itself, a multiple indicator approach, especially for personnel decisions, would seem to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

1982
1982
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 57 publications
0
19
0
2
Order By: Relevance
“…This is particularly true when the tool is carefully constructed and psychometrically tested before use (for examples, see Abrami, 2001;Theall & Franklin, 2001;Wachtel, 1998;Goldschmid, 1978;Marsh & Roche, 1997;and McKeachie, 1997).…”
Section: Government (Opening Remarks)mentioning
confidence: 99%
“…This is particularly true when the tool is carefully constructed and psychometrically tested before use (for examples, see Abrami, 2001;Theall & Franklin, 2001;Wachtel, 1998;Goldschmid, 1978;Marsh & Roche, 1997;and McKeachie, 1997).…”
Section: Government (Opening Remarks)mentioning
confidence: 99%
“…In other words, students of high rated lecturers will tend, other things being equal, to achieve more than students of less favourably rated lecturers. Though the conclusion is made that a relationship exists between student ratings and learning, the writer would like to enter a note of caution and to agree with Goldschmid (1978Goldschmid ( , 1976; Rose (1976); Whitely and Doyle (1976);and Meredith (1975), in suggesting a criterion-referenced measurement of student achievement. It is not just sufficient to use the final grades of students as the only criterion of achievement.…”
Section: Validity Of Student Ratingsmentioning
confidence: 99%
“…The result not only revealed a positive change in instructional rating by the students, but the students obtained higher class averages on measures of student motivation and a final common examination. Although the literature tends to favour the use of feedback as a means of improving instructional quality, authors such as Sherman and Winstead (1975), Frey (1976), Pohlman (1975), and Goldschmid (1978) have suggested that areas of instruction that require modification need to be specified. In addition to this suggestion, Rotem and Glasman (1977), have stipulated that lecturers requiring positive change as a result of feedback received must first of all show concern about the feedback and must be motivated to achieving the desired result -instructional improvement.…”
Section: Improvement Of Instruction and Teacher Effectivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…Le domaine de l'évaluation des apprentissages en éducation existe déjà depuis plusieurs années aux États-Unis comme au Québec (Goldschmid, 1978;Conseil Supérieur de l'Éducation, 1983 (Larose, 1985;Stufflebeam, 1968;Unesco, 1981;Stolovitch et Larocque, 1983;Jomphe et Adam 1984). "Aujourd'hui il nous faut une vision globale d'une situation d'enseignement pour compléter le processus décisionnel" (Ouellet, 1994).…”
Section: Introductionunclassified